The Influence of Economic Growth, Open Unemployment Rate, and Human Development Index on Poverty in East Java - Shaila, Feti Nur; Fitanto, Bahtiar (Journal of Development Economic and Social Studies, 2026)
Poverty is one of the fundamental issues in economic development, particularly in regions with complex social and economic dynamics such as East Java. This study examines poverty levels in East Java over the period 2018–2024. The objective of this research is to analyze the effects of Gross Regional Domestic Product (GRDP), the Open Unemployment Rate (OUR), and the Human Development Index (HDI), with the control variable Labor Force Participation Rate (LFPR) on the poverty rate. This study uses secondary data obtained from the Central Statistics Agency (BPS) with a quantitative approach using the Panel Data Regression analysis method. Based on the results of model selection tests, the Fixed Effect Model (FEM) is identified as the most appropriate model. The findings indicate that GRDP has a negative and statistically significant effect on poverty levels, while the Open Unemployment Rate has a positive and significant effect on poverty. Meanwhile, the Human Development Index exhibits a negative and significant influence on poverty. These findings are expected to provide valuable input for the formulation of poverty alleviation policies in East Java, ensuring that such policies are more targeted and sustainable.